Determinants of adopting improved bread wheat varieties in Arsi Highland, Oromia Region, Ethiopia: A Double-hurdle approach - Bedilu Demissie Zeleke; Adem Kedir Geleto; Hussien H. Komicha; Sisay Asefa (Cogent Economics & Finance, 2021)
The improvement of agricultural productivity using technology is an important avenue for increasing output and reducing poverty in sub-Saharan countries. However, the low adoption of high yield varieties has been identified as one of the main reasons for low productivity in sub-Saharan Africa. Consequently, the study examined the effect of demographic, socioeconomic and institutional factors affecting adoption and adoption-intensity of improved wheat varieties (IWVs), using data obtained from randomly selected farm households in the Arsi Highland of Ethiopia. We estimated a Double hurdle model to analyze the determinants of the intensity of IWVs adoption, as adoption and use intensity were two independent decisions influenced by different factors. The results also show that Double hurdle model is more appropriate than the Tobit model. Empirical estimates of the first hurdle reveal that wheat farming experience, distance to cooperatives, renting a tractor and combine harvester, Urea application, and net income from the wheat grain sale all significantly increased the likelihood of IWVs adoption. Estimates of the second hurdle revealed that the decision to use the optimal intensity of IWVs by smallholder farmers was influenced by seed availability, row planting, and distance to cooperative all significantly and positively. The intensity of adoption was also found to be negatively related to the proportion of farmland allotted for wheat production. Accordingly, policies and interventions that are informed about such factors are required to accelerate the adoption and adoption-intensity of IWVs in Ethiopia to realize a wheat Green Revolution and fight food insecurity in a sustainable manner.
Keywords: 330; Adoption; double hurdle model; Ethiopia; improved wheat varieties; tobit model